Síntese e caracterização de nanocompósitos ocos de Y2O3:Eu3+ revestidos com Fe3O4 - (:unkn) unknown (Universidade Federal de Goiás, 2020)
The study of hollow structures has stood out for being considered functional materials and due to their properties such as high load capacity, low density and high surface area. This set of factors allows the hollow structures to gain space in research for the production of new materials. Combined with these factors, luminescent and magnetic properties in a single material have been explored for their ability to track and visualize. Among the materials with luminescent properties, Y2O3:Eu3+ is highlighted as an important luminophore with red emission, easy to produce and with good stability. Among the magnetic materials, Fe3O4 stands out due to its compatibility with biological systems and its superparamagnetic behavior. In the present study, the synthesis and structural and morphological characterization for the production of hollow double hull spheres Y2O3:Eu3+@Fe3O4 was verified. To obtain these hollow structures of spherical morphology, the hard templating method was used, using carbon spheres obtained by the hydrothermal method, as a hard templating. The coprecipitation synthesis was used to coat the carbon spheres with Y2O3:Eu3+ and Fe3O4, and the resulting materials were subjected to heat treatment to remove carbon. The composites obtained have spherical and hollow morphology, based on the micrographs obtained by scanning electron microscopy with field emission (FEG), according to the X-ray diffraction, the structures were crystalline and presented phases related to Y2O3 and Fe3O4. The crystallite sizes were calculated providing evidence that Y2O3:Eu3+ and Fe3O4 nanoparticles covered the rigid model. The luminescent and magnetic properties were investigated and their results show compliance, the luminescent emissions characteristic of the Eu3+ ion in the 612nm region corresponding to the orange/red emission of the electromagnetic spectrum and superparamagnetic character due to the magnetic characteristics of Fe3O4.
Synthesis and characterization of nanocomposites hollow Y2O3: Eu3+ coated with Fe3O4
Keywords: Estruturas ocas; Y2O3:Eu3+; Fe3O4; Luminescentes; Magnéticas; Hollow spheres; Luminescent; Magnetic; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA INORGANICA::FISICO QUIMICA INORGANICA